Hybrid wireless-power line communication for indoor IoT networks - Zhu, Xu; Zhu, Kainan; Heggo, Mohammad (Artech House telecommunications and network engineering series., 2020)
This exciting resource covers the fundamentals of wireless and PLC technologies. Different types of wireless and PLC technologies used for indoor IoT applications are described. The channel models for both wireless and power line communications are introduced, highlighting the main challenges for these types of communications inside the indoor environment. The book explores the hybrid technologies with television white space (TVWS), very high frequency (VHF) wireless technology, and broadband PLC (BPLC) for indoor high speed IoT networks. A TVWS standardized BPLC system is proposed, which integrates the requirement of primary user sensing and the permissible transmission power spectral density (PSD) for TVWS users into BPLC standard, regarding VHF band access.The hybrid ultra-high frequency (UHF) wireless-powerline sensor networks with a focus on enlarging the network lifetime via cross-layer optimization is presented. Hybrid video sensor networks (HVSNs) with high data rate requirement are explored. Through the joint design of video encoding rate, aggregate power consumption, channel access control, along with link rate allocation, a distributed algorithm is developed, which divides the computational burden among all nodes with much lower communication overhead. The effectiveness of the cross-layer designs are evaluated through extensive simulation results.